STIRLING ENGINE: FROM DESIGN TO APPLICATION INTO PRACTICE AND EDUCATION - Thanh Le, Hien; Nghia, Huynh Hoang; Huy, Bui Minh; Phu, Vu Thanh; Quyen, Vy Bui Hoang (AUSTENIT, 2022)
Stirling motor is a type of outside ignition heat motor that can utilize various fuel sources from customary structures (coal, oil, kindling, rice husk, and so forth) to sustainable power sources (sun-oriented energy), climate, squander heat usage, and so forth). The article centers around introducing the fundamental highlights of the improvement history, activity qualities, and plan techniques for certain sorts of Stirling motors, in this way offering useful appropriateness as well as a college preparing for understudies. The understudy studying Thermal Engineering in our nation today. Â  Â